2021
DOI: 10.26440/ihrj/0411.02393
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Root Resorption in Correction of Class II Malocclusion

Abstract: INTRODUCTION: External apical root resorption is a common iatrogenic side effect of orthodontic treatment and has been reported particularly in anterior teeth. The etiology of resorption is multifactorial, complex and individual susceptibility to resorption depends on various factors.MATERIALS AND METHOD: The degree of root resorption during orthodontic treatment was evaluated on the post-treatment RVGs of the maxillary and mandibular central and lateral incisors of 28 skeletal Class II patients with mandible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The changes in the tooth inclinations were also measured before and after treatment and the results stated a statistically significant difference thereby depicting an increase in the inclination of the mandibular anterior teeth (p=0.005). These findings were in accordance with the previous study by [18]. Hence the use of Advansync2 appliance for correction of class II malocclusions could also lead to root resorption and increased inclination of the mandibular anteriors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The changes in the tooth inclinations were also measured before and after treatment and the results stated a statistically significant difference thereby depicting an increase in the inclination of the mandibular anterior teeth (p=0.005). These findings were in accordance with the previous study by [18]. Hence the use of Advansync2 appliance for correction of class II malocclusions could also lead to root resorption and increased inclination of the mandibular anteriors.…”
Section: Discussionsupporting
confidence: 93%
“…According to a systematic evaluation, most incisors with treated Class II division 1 malocclusions had mild to moderate OIIRR [17]. Previous research has also demonstrated that there could be alveolar bone loss and successive loss of tooth in case of severe inclination of incisors buccally or lingually [18]. Rekhawat et.…”
Section: Discussionmentioning
confidence: 99%